Strategi Peningkatan Kompetensi Guru melalui Program Pengembangan Profesional Berkelanjutan di sekolah Dasar Negeri 07 Rantau Alai - Febrianti Febrianti; Meilia Rosani; Mahasir Mahasir (Pusat Riset dan Inovasi Nasional, 2025)
Improving the quality of education is highly dependent on teacher competence as the main implementer of the learning process. In the dynamic modern era, teachers are required to continue to improve their professionalism and pedagogical skills in order to be able to face the challenges of the curriculum and the development of educational technology. However, in several elementary education units, including State Elementary School 07 Rantau Alai, there are still teachers who experience competency gaps, both in pedagogical, professional, and social aspects. This encourages the need for an appropriate strategy in an effort to improve teacher competence in a sustainable manner. This study aims to describe the strategy for improving teacher competence through the Continuing Professional Development Program (PPPB) at State Elementary School 07 Rantau Alai. This study also focuses on the form of implementation, effectiveness of the strategy, and supporting and inhibiting factors in the implementation of the program. The method used in this study is a qualitative approach with a case study type. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation studies. The subjects of the study included principals, teachers, and school supervisors. The data obtained were analyzed descriptively qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the strategy for improving teacher competence through PPPB is carried out through internal training, routine coaching, and collaboration with teacher learning communities. This program has been proven to have a positive impact on improving teacher professionalism in designing and implementing learning. The main obstacles in implementation are limited time and facilities, but are supported by high teacher motivation and active principal leadership.